(3eONd ddJMdjd GdfbOj (B/s - (3MejOGJ, eMehOs ((3GdLRGFQ(B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 2000)
(3GdfbO hGdEFJeGf hCSYGQ GdaGFOI,CSYGQ GdUQa,SjGSI CSYGQ GdUQa,GdfXGe GdeUQaj GdLRGFQj,fXGe GdUQa aj GdLRGFQ,fXGe GdQbGHI Ydi GdUQa aj GdLRGFQ(B.s
(3GdeQGLY U(B.213 (3GdLOGhd U(B. 195s
Keywords: (3GdfbhOs